Effects of landscape pattern change on ecosystem services and its interactions in karst cities: A case study of Guiyang City in China - Shujun Liu; Zhijie Wang; Wu Wu; Lifei Yu (Ecological Indicators, 2022)
Exploring the effects of landscape pattern changes on ecosystem services (ESs) and its interactions could provide a new method to reduce the trade-offs between ESs from the perspective of landscape pattern optimization, thus contributing to the sustainable management of ESs. In this study, the Guiyang City which is a typical karst mountainous city in China was used as the study region, using InVEST model, Spearman’s correlation and Multiscale Geographically Weighted Regression (MGWR) model, the study assessed the changes and trade-offs of four key types of ESs (i.e., carbon storage (CS), habitat quality (HQ), soil conservation (SC), water yield (WY)) from 1995 to 2019, and analyzed the impacts of landscape pattern on the synergies of ESs. The results showed that ESs in Guiyang City steadily increased during 1995–2019, with CS, HQ, SC, WY, and total ecosystem services (TES) increased by 6.67%, 7.66%, 27.16%, 13.08%, and 11.81%, respectively. The relationship of CS-SC and SC-WY were mainly trade-offs, while the other ESs types were mainly synergies. Moreover, the interaction of static ESs was reversed with that of dynamic spatiotemporal ESs when the lower interaction relationship between static ESs. The effects of landscape pattern changes on ESs and ESs interactions have obvious spatial and scale heterogeneity. Landscape composition had a greater impact on ESs than landscape configuration. Proportion of woodland (Wood_per) and Shannon’s Diversity Index (SHDI) were the main factors influencing the synergies effect of TES. The results could provide practical references for ESs improvement-oriented landscape pattern planning and ecosystem service management in the Guiyang City and in similar fragile ecological regions, which is helpful for the improvement of ESs and high-quality sustainable development.